ATF2 loss promotes tumor invasion in colorectal cancer cells via upregulation of cancer driver TROP2 - Hübner, Kerstin; Erlenbach-Wünsch, Katharina; Prochazka, Jan; Sheraj, Ilir; Hampel, Chuanpit; Mrazkova, Blanka; Michalcikova, Tereza; Tureckova, Jolana; Iatsiuk, Veronika; Weissmann, Anne; Ferrazzi, Fulvia; Kunze, Philipp; et al. (Cellular and Molecular Life Sciences, 2022)
In cancer, the activating transcription factor 2 (ATF2) has pleiotropic functions in cellular responses to growth stimuli, damage, or inflammation. Due to only limited studies, the significance of ATF2 in colorectal cancer (CRC) is not well understood. We report that low ATF2 levels correlated with worse prognosis and tumor aggressiveness in CRC patients. NanoString gene expression and ChIP analysis confirmed trophoblast cell surface antigen 2 (TROP2) as a novel inhibitory ATF2 target gene. This inverse correlation was further observed in primary human tumor tissues. Immunostainings revealed that high intratumoral heterogeneity for ATF2 and TROP2 expression was sustained also in liver metastasis. Mechanistically, our in vitro data of CRISPR/Cas9-generated ATF2 knockout (KO) clones revealed that high TROP2 levels were critical for cell de-adhesion and increased cell migration without triggering EMT. TROP2 was enriched in filopodia and displaced Paxillin from adherens junctions. In vivo imaging, micro-computer tomography, and immunostainings verified that an ATF2(KO)/TROP2(high) status triggered tumor invasiveness in in vivo mouse and chicken xenograft models. In silico analysis provided direct support that ATF2(low)/TROP2(high) expression status defined high-risk CRC patients. Finally, our data demonstrate that ATF2 acts as a tumor suppressor by inhibiting the cancer driver TROP2. Therapeutic TROP2 targeting might prevent particularly the first steps in metastasis, i.e., the de-adhesion and invasion of colon cancer cells.
CRIS-Team WoS Importer:2022-07-29

Inhibition of TRPM7 blocks MRTF/SRF-dependent transcriptional and tumorigenic activity - Voringer, Sandra; Schreyer, Laura; Nadolni, Wiebke; Meier, Melanie; Woerther, Katharina; Mittermeier, Constanze; Ferioli, Silvia; Singer, Stephan; Holzer, Kerstin; Zierler, Susanna; Chubanov, Vladimir; Liebl, Bernhard; et al. (Oncogene, 2019)
Myocardin-related transcription factors A and B (MRTFs) are coactivators of Serum Response Factor (SRF) that mediates the expression of genes involved in cell proliferation, migration and differentiation. There is mounting evidence that MRTFs and SRF represent promising targets for hepatocellular carcinoma (HCC) growth. Since MRTF-A nuclear localization is a prerequisite for its transcriptional activity and oncogenic properties, we searched for pharmacologically active compounds able to redistribute MRTF-A to the cytoplasm. We identified NS8593, a negative gating modulator of the transient receptor potential cation channel TRPM7, as a novel inhibitor of MRTF-A nuclear localization and transcriptional activity. Using a pharmacological approach and targeted genome editing, we investigated the functional contribution of TRPM7, a unique ion channel containing a serine-threonine kinase domain, to MRTF transcriptional and tumorigenic activity. We found that TRPM7 function regulates RhoA activity and subsequently actin polymerization, MRTF-A-Filamin A complex formation and MRTF-A/SRF target gene expression. Mechanistically, TRPM7 signaling relies on TRPM7 channel-mediated Mg2+ influx and phosphorylation of RhoA by TRPM7 kinase. Pharmacological blockade of TRPM7 results in oncogene-induced senescence of hepatocellular carcinoma (HCC) cells in vitro and in vivo in HCC xenografts. Hence, inhibition of the TRPM7/MRTF axis emerges as a promising strategy to curb HCC growth.
CRIS-Team Scopus Importer:2019-12-27

LPA-induced phosphorylation of Filamin A regulates association with Myocardin-related transcription factor A (MRTF-A) and cellular senescence - Konopa, Andreas; Meier, Melanie; Mühlich, Susanne (NAUNYN-SCHMIEDEBERGS ARCHIVES OF PHARMACOLOGY, 2022)
CRIS-Team WoS Importer:2022-04-15

LPA receptor 1 (LPAR1) is a novel interaction partner of Filamin A that promotes Filamin A phosphorylation, MRTF-A transcriptional activity and oncogene-induced senescence - Konopa, Andreas; Meier, Melanie; Franz, Miriam; Bernardinelli, Emanuele; Vögele, Anna-Lena; Atreya, Raja; Ribback, Silvia; Roessler, Stephanie; Aigner, Achim; Singer, Kerstin; Singer, Stephan; Sarikas, Antonio; et al. (Oncogenesis, 2022)
Myocardin-related transcription factors A and B (MRTFs) are coactivators of Serum Response Factor (SRF), which controls fundamental biological processes such as cell growth, migration, and differentiation. MRTF and SRF transcriptional activity play an important role in hepatocellular carcinoma (HCC) growth, which represents the second leading cause of cancer-related mortality in humans worldwide. We, therefore, searched for druggable targets in HCC that regulate MRTF/SRF transcriptional activity and can be exploited therapeutically for HCC therapy. We identified the G protein-coupled lysophosphatidic acid receptor 1 (LPAR1) as a novel interaction partner of MRTF-A and Filamin A (FLNA) using fluorescence resonance energy transfer-(FRET) and proximity ligation assay (PLA) in vitro in HCC cells and in vivo in organoids. We found that LPAR1 promotes FLNA phosphorylation at S2152 which enhances the complex formation of FLNA and MRTF-A, actin polymerization, and MRTF transcriptional activity. Pharmacological blockade or depletion of LPAR1 prevents FLNA phosphorylation and complex formation with MRTF-A, resulting in reduced MRTF/SRF target gene expression and oncogene-induced senescence. Thus, inhibition of the LPAR1-FLNA-MRTF-A interaction represents a promising strategy for HCC therapy.
CRIS-Team WoS Importer:2023-01-13

Tetraspanin 5 (Tspan5), a novel gatekeeper of the tumor suppressor dlc1 and myocardin-related transcription factors (mrtfs), controls hcc growth and senescence - Schreyer, Laura; Mittermeier, Constanze; Franz, Miriam; Meier, Melanie; Martin, Dietmar E.; Maier, Kerstin C.; Hübner, Kerstin; Schneider-Stock, Regine; Singer, Stephan; Holzer, Kerstin; Fischer, Dagmar; Ribback, Silvia; et al. (Cancers, 2021)
Human hepatocellular carcinoma (HCC) is among the most lethal and common cancers in the human population, and new molecular targets for therapeutic intervention are urgently needed. Deleted in liver cancer 1 (DLC1) was originally identified as a tumor suppressor gene in human HCC. DLC1 is a Rho-GTPase-activating protein (RhoGAP) which accelerates the return of RhoGTPases to an inactive state. We recently described that the restoration of DLC1 expression induces cellular senescence. However, this principle is not amenable to direct therapeutic targeting. We therefore performed gene expression profiling for HepG2 cells depleted of DLC1 to identify druggable gene targets mediating the effects of DLC1 on senescence induction. This approach revealed that versican (VCAN), tetraspanin 5 (TSPAN5) and N-cadherin (CDH2) were strongly upregulated upon DLC1 depletion in HCC cells, but only TSPAN5 affected the proliferation of HCC cells and human HCC. The depletion of TSPAN5 induced oncogene-induced senescence (OIS), mediated by the p16INK4a/pRb pathways. Mechanistically, silencing TSPAN5 reduced actin polymerization and thereby myocardin-related transcription factor A-filamin A (MRTF-A-FLNA) complex formation, resulting in decreased expression of MRTF/SRF-dependent target genes and senescence induction in vitro and in vivo. Our results identify TSPAN5 as a novel druggable target for HCC.
CRIS-Team Scopus Importer:2021-11-05
Keywords: DLC1; MKL1; MRTF; SRF; TSPAN5